Clinical study of a new nutritional index for predicting long-term prognosis in patients with coronary atherosclerotic heart disease following percutaneous coronary intervention - Chu Xinqiu; Yuan Yuewen; Chen Jiya; Yu Yanwei; Li Yang (Frigid Zone Medicine)
Some patients continue to experience major adverse cardiovascular and cerebrovascular events (MACCE) after percutaneous coronary intervention (PCI) in frigid places. Indexes of inflammation and nutrition alone were shown to predict outcomes in patients with PCI. However, the clinical predictive value of mixed indicators is unclear. This study aimed to assess the predictive value of the albumin/neutrophil/lymphocyte ratio (NLR) on the long-term prognosis of patients with coronary heart disease (CHD) following percutaneous coronary intervention (PCI).